ANALISIS FAKTOR-FAKTOR KEBERMAKNAAN HIDUP REMAJA DI PANTI ASUHAN DHARMA IBU MUARA BULIAN - Putri, Duwi; A Rahman, K.; Susanti, Desy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This Study examines the factors of meaning in life (kebermaknaan hidup) among adolescents residing at Panti Asuhan Dharma Ibu Muara Bulian, grounded in Viktor E. Frankl’s logotherapy theory. A qualitative phenomenological approuch was employed adolescent informants (RS and LH), both aged 13-18 years, orphaned, and residing at the orphanage for a minimum of two years. Data were collected through in-depth semi-structured interviews, passive participatory observation, and documentation, then analyzed using the interactive model of Miles and Huberman. The findings reveal that both informants found meaning in life through Frankl's three value dimensions: creative values (through daily responsibilities, social contributions, and personal achievements), experiential values (through religious activities, peer relationships, and deep gratitude), and attitudinal values (through acceptance of loss, stigma, and an uncertain future). Supporting factors include peer social support as a surrogate family system, religious and spiritual activities, access to education, clear future aspirations, and meaningful figures who provide inner strength. Inhibiting factors include fear and low self-confidence, longing and loneliness due to separation from family, limited mobility and orphanage facilities, social stigma from the external environment, and an authoritarian caregiving pattern that restricts emotional expression. These findings confirm that meaning in life can be achieved even under profound limitation.